Prevalence, time trends and treatment practices of asthma in India: the Global Asthma Network study. Issue 2 (30th May 2022) - Singh, Sheetu; Salvi, Sundeep; Mangal, Daya Krishan; Singh, Meenu; Awasthi, Shally; Mahesh, Padukudru Anand; Kabra, Sushil K.; Mohammed, Sabir; Sukumaran, Thevaruparambil U.; Ghoshal, Aloke G.; Barne, Monica; Sinha, Sanjeev; et al.
Objective: The objective of this subanalysis of data from centres across urban areas in India of the Global Asthma Network (GAN) was to study 1) the prevalence of symptoms of asthma in children and adults, 2) the change in prevalence of asthma and its trigger factors since the International Study of Asthma and Allergies in Childhood (ISAAC), and 3) current asthma treatment practice. Methods: In this cross-sectional, multicentre, school-based and self-administered questionnaire, responses from children aged 6–7 years and 13–14 years, and their respective parents, were analysed. Results: The GAN Phase I study included 20 084 children in the 6–7-year age group, 25 887 children in the 13–14-year age group and 81 296 parents. The prevalence of wheeze in the previous 12 months was 3.16%, 3.63% and 3.30% in the three groups, respectively. In comparison to the ISAAC studies, there was a significant reduction in the prevalence of current wheeze (p<0.001). Bivariate analysis revealed a significant reduction in the prevalence of trigger factors. Almost 82% of current wheezers and 70% of subjects with symptoms of severe asthma were not clinically diagnosed as having asthma. The daily use of inhaled corticosteroids (ICS) was less than 2.5% in subjects with current wheeze and those with symptoms of severe asthma but less than 1% used daily ICS when asthma remained undiagnosed. Conclusion: The prevalence of current wheeze and its causal factors showed a significant reduction compared to previous ISAAC studies. Among subjects with current wheeze and symptoms of severe asthma, the problem of under-diagnosis and under-treatment was widespread. Data from Indian centres that participated in the multicentre Global Asthma Network showed a significant decline in symptoms of asthma compared to previous studies. The study highlighted under-diagnosis and under-treatment in children and adults with asthma. https://bit.ly/3thevot